2022
DOI: 10.3390/ijerph19159277
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Color and Brightness of White Spots Associated with Orthodontic Treatment 6 Months after the Application of Infiltrative Resins: Systematic Review and Meta-Analysis

Abstract: One of the risks that we find after orthodontic treatment is the secondary appearance of white spot lesions (WLS) after the removal of fixed multi-bracket appliances. Today, there are several treatment methods, resin infiltration being the most used in the most serious cases. The objective of this study is to carry out a systematic review and meta-analysis to determine the efficacy and stability in the variables of color and gloss, six months after resin infiltration. A comprehensive search was performed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…[ 26 ] In deeper lesions, infiltration is more difficult because the pores are narrower and debris, saliva, organic material, and air may be present in the pores, making resin infiltration into the porous enamel more difficult. [ 27 ] This contradicts the findings of Ou et al ,[ 28 ] who investigated the impact of resin infiltration on enamel demineralization to varying degrees. The outcomes showed that both low- and high-enamel demineralization interventions had comparable concealing effects.…”
Section: Discussionmentioning
confidence: 82%
“…[ 26 ] In deeper lesions, infiltration is more difficult because the pores are narrower and debris, saliva, organic material, and air may be present in the pores, making resin infiltration into the porous enamel more difficult. [ 27 ] This contradicts the findings of Ou et al ,[ 28 ] who investigated the impact of resin infiltration on enamel demineralization to varying degrees. The outcomes showed that both low- and high-enamel demineralization interventions had comparable concealing effects.…”
Section: Discussionmentioning
confidence: 82%